2011
DOI: 10.1007/s00464-011-1961-1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of surgical procedures for symptomatic fundoplication failure: a retrospective case–control study

Abstract: Compared to primary antireflux surgery, revisional operations are associated with longer mean operating times, increased length of hospital stay, and increased morbidity. Despite this fact, the majority of patients are satisfied with the outcomes of revisional surgery for failed fundoplication, and symptomatic outcomes are good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…This reduction in QOL is potentially likely due to further alterations in the local anatomy and deterioration in esophageal function. These findings are similar to those by Musunuru and Gould [11], who compared laparoscopic reoperative ARS vs controls and confirmed that Visick and satisfaction scores are lower in the reoperative group, and to the study by Little and colleagues [7] that showed worse outcomes with open operations in patients undergoing two or more operations. These results suggest that procedures other than an antireflux operation should be considered if an initial reoperation fails.…”
Section: Commentsupporting
confidence: 87%
See 4 more Smart Citations
“…This reduction in QOL is potentially likely due to further alterations in the local anatomy and deterioration in esophageal function. These findings are similar to those by Musunuru and Gould [11], who compared laparoscopic reoperative ARS vs controls and confirmed that Visick and satisfaction scores are lower in the reoperative group, and to the study by Little and colleagues [7] that showed worse outcomes with open operations in patients undergoing two or more operations. These results suggest that procedures other than an antireflux operation should be considered if an initial reoperation fails.…”
Section: Commentsupporting
confidence: 87%
“…The rate of reoperation (8%) and the predominant type of failure is similar to other studies [4,6,8,11]. Although often difficult to ascertain, failure of the hiatal closure appears to be a large contributor to most ARS failures.…”
Section: Commentsupporting
confidence: 83%
See 3 more Smart Citations